ANALISIS KELAYAKAN FINANSIAL, NILAI TAMBAH DAN STRATEGI PENGEMBANGAN KOMODITAS SALAK DI KABUPATEN JEMBER - Viana Indarwati; Soetriono Soetriono; Sudarko Sudarko (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2015)
This research intended to know the suitable zalacca agriculture industrialism through financial method; to know the sensitivity of zalacca agriculture industrialism; to know the amount value of zalacca processing become “dodol salak; and to know the strategy commodity zallaca development. The location of the research is determined by purposive method. The sampling method in this research is taken by Simple Random Sampling and key person. The data that is used are primary data and secondary data. The analysis data is used are; (1) the suitable financial, the sensitivity analysis, the amount value analysis, and force field analysis. The result analysis show that: the zalacca agriculture industrialism through financial method is workable; the zalacca agriculture industrialism does not sensitive with any change; the tabulation zalacca become “dodol salak” can give the amount value; the development strategy should be formulated by assembled the farmer to take care the zalacca intensively and to inform that related with the benefit zalacca process and marketing product, it held contiguous for zalacca processing with diversification tabulation for supporting home industry when it is not zalacca season.Keywords: Zalacca, suitable financial, sensitivity analysis